Long-read sequencing reveals the shell microbiome of apparently healthy American lobsters Homarus americanus from Atlantic Canada - Koepper, Svenja; Clark, K. Fraser; McClure, J. Trenton; Revie, Crawford W.; Stryhn, Henrik; Thakur, Krishna K. (Frontiers in Microbiology, 2023)
The shell microbial community of lobstersa key factor in the development of epizootic shell disease (ESD)is still insufficiently researched in Atlantic Canada and many knowledge gaps remain. This study aimed to establish a baseline description and analysis of the shell microbiome of apparently healthy lobsters from four locations in the region. More than 180 lobster shell swab samples were collected from New Brunswick, Nova Scotia and Prince Edward Island (PEI). PacBio long-read 16S rDNA sequencing and bioinformatic analyses in QIIME2 identified the shellassociated bacteria. The shell microbiome of healthy lobsters consisted mainly of the bacterial classes Gammaproteobacteria, Saprospiria, Verrucomicrobiae, Alphaproteobacteria, Flavobacteriia, Acidimicrobiia and Planctomycetia. The microbial composition differed regionally and seasonally, with some classes showing decreased or increased relative abundances in the PEI samples as well as in the winter and spring samples in Nova Scotia. The core shell microbiome included potentially pathogenic as well as beneficial bacterial taxa, of which some were present only in certain regions. Bacterial taxa that have previously been associated with ESD were present on healthy lobsters in Atlantic Canada, but their frequency differed by location, sampling time, and moult stage. This study indicated that geographical and seasonal factors influenced the shell microbiome of apparently healthy lobsters more than host factors such as sex, size, and moult stage. Our results provide valuable reference microbial data from lobsters in a disease-free state.Next-generation sequencing and faster computational methods have advanced microbial research in animals and humans over the past couple of decades. Multiple studies have highlighted the important influence of microbial communities on their host's metabolism, growth, and immune functions (